THE ROLE OF AWEWE (WOMAN) IN KAMPUNG NAGA TASIKMALAYA - Recita Widyan Morteza; Adelia Lintang Anjarika; Mamat Supriatna (Marwah: Jurnal Perempuan, Agama dan Jender, 2026)
Women in indigenous communities play a strategic role in maintaining family life and preserving cultural values. This study aims to examine the dual role of women in domestic and economic life, particularly in the context of the indigenous community of Kampung Naga. The research method used is a qualitative approach with a descriptive-analytical design. Data was obtained through field observations, in-depth interviews, and literature studies to understand gender role division and women's contributions within the family. The results show that women not only play a major role as household managers and educators of cultural values within the family, but also contribute significantly to supporting the family economy through various productive activities based on the household and culture. This dual role is an important foundation for the economic, social, and cultural stability of the family, even though it often does not receive equal recognition. This study concludes that the recognition and strengthening of women's dual roles is very important in efforts to preserve traditional values and sustainable family development amid social change.   Keywords: kampung naga, role, women.